2021
DOI: 10.1021/acsami.1c02064
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Li/Fluorinated Graphene Primary Batteries with High Energy Density and Power Density

Abstract: Lithium/fluorinated carbon (Li/CF x ) primary batteries have essential applications in consumer electronics and medical and high-power military devices. However, their application is limited due to the difficulty in achieving simultaneous high power density and high energy density in the CF x cathode. The tradeoff between conductivity and fluorine content is the decisive factor. Herein, by rational design, 3D porous fluorinated graphene microspheres (FGS-x) with both high conductivity and a high F/ C ratio are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 54 publications
4
48
0
Order By: Relevance
“…It is not unexpected to find that the assembled Li||CF x battery exhibits an attenuated capacity of 707 mAh g –1 and an energy density of 1809 Wh kg –1 with an average discharge voltage of 2.56 V in the conventional electrolyte (1 M LiPF 6 , EC/DEC) (Figure e). As shown in FTIR spectra (Figure S3a), the peak related to semi-ionic (SI) C–F bonds at about 1300 cm –1 is weakened in the sample of soaked CF x (by TEA solvent). In addition, a new peak at about 1450 cm –1 appears, which could be assigned to the C–N bonds .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It is not unexpected to find that the assembled Li||CF x battery exhibits an attenuated capacity of 707 mAh g –1 and an energy density of 1809 Wh kg –1 with an average discharge voltage of 2.56 V in the conventional electrolyte (1 M LiPF 6 , EC/DEC) (Figure e). As shown in FTIR spectra (Figure S3a), the peak related to semi-ionic (SI) C–F bonds at about 1300 cm –1 is weakened in the sample of soaked CF x (by TEA solvent). In addition, a new peak at about 1450 cm –1 appears, which could be assigned to the C–N bonds .…”
Section: Resultsmentioning
confidence: 92%
“…Extensive efforts have been focused on improving the electrochemical performance of CF x materials, including optimization of the fluorination process, , construction of nanostructures, and surface engineering of bulk materials. The effects of fluorination conditions (fluorination temperature, especially) on discharge capacity and voltage plateau were studied by Feng et al It was found that the F/C ratios of fluorinated hard carbon increased, while the discharge plateau inversely decreased as a function of fluorination temperature. In spite of the highest specific capacity of 922.6 mAh g –1 of fluorinated hard carbon obtained at 390 °C, the sacrificial discharge potential is about 0.15 V compared with that fluorinated at 350 °C, which limited the improvement of energy density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 displays the recorded XPS spectra of C1s, F1s, and their Gaussian shape decompositions for the untreated CF x and H−CF x (see detailed XPS peak fittings and assignments in Table S1). In the C1s spectra, the series of peaks from high to low binding energies are assigned to the species of preserved F 2 C(CF) 2 , FC(CF) 3 , sp 3 -type FC(C) 3 , C(CF) n , and sp 2 -type C−C. 16,29 In Figure 2b, the peak at 283 eV was assigned to the formed −CH 3 bond due to hydrogen introduction, 30 consistent with the above etching mechanism expressed in eq 2.…”
Section: Resultsmentioning
confidence: 99%
“…The Li/CF x battery has the highest specific energy density (theoretical value of 2180 Wh/kg) among the existing lithium primary batteries such as Li/MnO 2 , Li/SO 2 , and Li/SOCl 2 batteries. Also, the Li/CF x battery has excellent high and low temperature performance, high reliability, stable working voltage, long service life, low self-discharge, and other obvious advantages. Thus, it has been widely deployed in commercial, aerospace, medical, and military markets. However, due to the strong covalent C–F bond, the CF x material has a low electronic conductivity, which leads to electrode polarization and reduces the rate discharge performance.…”
Section: Introductionmentioning
confidence: 99%